Photobleaching Lifetimes of Cyanine Fluorophores Used for Single‐Molecule Förster Resonance Energy Transfer in the Presence of Various Photoprotection Systems. Issue 9 (3rd June 2013) - Cooper, David; Uhm, Heui; Tauzin, Lawrence J.; Poddar, Nitesh; Landes, Christy F.
<x xml:space="preserve">Abstract</x> Lengthening smFRET lifetimes: We investigated various photoprotection system combinations to find the combination that optimally extended the photobleach lifetime of a Cy3/Cy5 smFRET pair attached to a DNA hairpin in a single‐molecule environment. We found that the glucose/glucose oxygen‐scavenging solution in combination with redox‐based photostabilization solutions yielded the longest average photobleaching lifetimes.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>